Analyzing Spotify in Azerbaijan Using a Unified Theory of Acceptance and Use of Technology 2 - Zeynalov, Sabir (Digital Repository of Theses, 2024)
The emergence of music streaming services has been an essential breakthrough in music technology in the era of digitalization. Despite the large number of players in the global market, the Spotify platform has the leading position. By the end of 2023, Spotify had more than 602 million active users and operated in more than 180 markets. Despite the global popularity and spread of music streaming services, limited literature examines the acceptance and use of this technology. Several studies suggest using UTAUT2 to analyze Spotify users' adoption (Walean and Rachmawati, 2018; Chandra et al., 2018; Amalina, 2019; Suhod et al., 2022).Venkatesh et al. (2012) suggest testing UTAUT2 in different countries, age groups, and technologies, which helps to improve the applicability of this model in the context of technology adoption. Therefore, this study comprehensively analyzes the adoption of the music streaming service Spotify in Azerbaijan using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. Using a quantitative methodology, this study initially collected primary data from Spotify users living in Azerbaijan through a survey. The 5-point Likert scale responses were analyzed using the PLS-SEM techniques. The study results showed that the proposed factors of the theoretical construct UTAUT2, performance expectancy (PE), effort expectancy (EE), price value (PV), and habit (H), had a significant positive impact; however, social influence (SI) had a negative effect on the behavioral intention (BI) of Spotify users in Azerbaijan. Obtained results on the influence of several UTAUT2 determinants on the behavioral intention of Spotify users in Azerbaijan provide a comprehensive ground for developing further business strategies and optimizing the user experience of Spotify in the territory of Azerbaijan. Based on the findings of this investigation, Spotify can maintain its dominant position in the highly competitive music streaming market in Azerbaijan by attracting more new customers and retaining loyal customers more effectively.